How students utilize social media in achieving academic success? / Fadhli Dzil Ikram Ishak ... [et al.] - Ishak, Fadhli Dzil Ikram; Md Shahfri Rozaini, Muhammad Shahamir Fitri; Khairudin, Norhaziq Khairina; Noramin, Nur Azreena Balqis; Norhairul Hizam, Umar Aun Amru; Hassan, Mohd Sufiean (Faculty of Communication & Media Studies, 2023)
This study aims to find out how students utilize social media to achieve academic success. Social media influences can bring positive and negative effects on people. It can be used for entertainment, work, research and even for school work. The methodology that is used to analyze how social media are affected towards achieving academic success is based on the questionnaires that consisted of 12 questions that used a five-point Likert scale and were distributed online using Google Forms. The total respondents for this survey is 162 people. The findings of the study revealed that social media are mostly used for entertainment purposes and they have also influenced a lot of their studies. Most respondents also agree that they use social media as their research engine to conduct research for assignments and read educational articles. It is evidently clear that academic success can be achieved if students utilize social media correctly.